Optimal Sale of a Commodity Stockpile - Kupperman, Robert H.; Smith, Harvey A. (Management Science, 1970)
The problem of maximizing the present value of the return from sale of a commodity stockpile is solved for a linear Walrasian market. Approximations and bounds are given and the practical utility of knowing the solution is discussed. The impact of such sales on the producing industry and the distribution of this impact are also studied. Mossin in [Mossin, Jan. 1966. On a class of optimal stock depletion policies. Management Sci. 13(1, September).] has solved an allied problem having a special case in common with the one treated here.